Various Technical Aspects in Herbal Tea Production from Alisma Plantago-Aquatica Leaf - N. P. Minh (Journal of Global Pharma Technology, 2016)
Alisma plantago-aquatica is abundant weed on thinned crops of rice. A. plantago-aquatica is resistant to flood, but being very susceptible to shade; therefore the thickened rice crops shade the weeds and detain their growth. Leaves green; lower ones only sessile, widely linear, and swimming; the other ones aerial, long-petiolate; their plates big, ovoid or widely ovoid, with cordate base usually, with pointed apex. The use of medicinal herbs as a source of antioxidants is significant because they are often utilized to heal chronic diseases. Objective of this study focused on the effectiveness of blanching temperature and time; oven drying temperature and storage condition to total phenolics (mg/g), total flavonoids (mg/g), ferric reducing/antioxidant power (FRAP, mg/g), radical-scavenging activity (DPPH, mg/mL) of the dried Alisma plantago-aquatica tea. Results showed that Alisma plantago-aquatica should be treated in hot water at 95oC within 8 seconds in the present of citric acid 1.0% and then being dried by drying oven at 45oC until 7.5% moisture. The final herbal tea could be preserved under vacuum in aluminum bag at 28oC to maintain total phenolics, total flavonoids, antioxidant power and radical-scavenging activity for 12 months.Keywords: Alisma plantago-aquatica, Phenolic, Flavonoid, Herbal, FRAP, DPPH, Blanching, Drying.